Autoimmune/inflammatory syndrome induced by adjuvants (ASIA) after silicone breast implants - Jaouad Yousfi; Soukaina Oumlil; Lamiaa Essaadouni (European Journal of Case Reports in Internal Medicine)
Autoimmune/inflammatory syndrome is a complex condition characterized by various autoimmune and inflammatory symptoms following the exposure to an adjuvant such as silicone. Autoimmune/inflammatory syndrome induced by adjuvants (ASIA) is challenging to diagnose because it can mimic other autoimmune diseases and requires specific criteria for identification. We report a case of a 35-year-old woman who developed inflammatory joint pain, fatigue and myalgia after receiving silicone breast implants. Symptoms improved significantly after administration of steroids. Based on the fulfilment of the ASIA diagnostic criteria, the diagnosis was made. This case emphasizes the importance of understanding this condition in patients with unexplained systemic symptoms after exposure to adjuvants.